Cyclophilin A and Ess1 interact with and regulate silencing by the Sin3–Rpd3 histone deacetylase - Arévalo-Rodríguez, Miguel (Oxford University Press, 2000)
Three families of prolyl isomerases have been identified: cyclophilins, FK506-binding proteins (FKBPs) and parvulins. All 12 cyclophilins and FKBPs are dispensable for growth in yeast, whereas the one parvulin homolog, Ess1, is essential. We report here that cyclophilin A becomes essential when Ess1 function is compromised. We also show that overexpression of cyclophilin A suppresses ess1 conditional and null mutations, and that cyclophilin A enzymatic activity is required for suppression. These results indicate that cyclophilin A and Ess1 function in parallel pathways and act on common targets by a mechanism that requires prolyl isomerization. Using genetic and biochemical approaches, we found that one of these targets is the Sin3–Rpd3 histone deacetylase complex, and that cyclophilin A increases and Ess1 decreases disruption of gene silencing by this complex. We show that conditions that favor acetylation over deacetylation suppress ess1 mutations. Our findings support a model in which Ess1 and cyclophilin A modulate the activity of the Sin3–Rpd3 complex, and excess histone deacetylation causes mitotic arrest in ess1 mutants.